The Impact of Technology Developments on Legal Practice: Challenges for Advocates in the E-Court Era - Dryland, Enya; Siregar, Hisar (Manunggal Halim Jaya, 2025)
The rapid development of information technology in recent decades has had a significant impact on various sectors, including the legal sector. One of the main impacts is the implementation of the e-Court system, which is a digitization of court procedures starting from case registration, fee payment, to trial that can be done online. This innovation is designed to overcome various challenges faced by the conventional justice system, such as convoluted bureaucracy, length of case resolution, and limited access for the general public. E-Court plays a role in improving the efficiency, transparency, and accessibility of legal processes. However, in addition to the various benefits it offers, the implementation of e-Court also brings new challenges, especially for advocates who need to adapt to the development of this technology. this study aims to analyze the impact of technology on legal practice, with a particular focus on the roles and challenges faced by advocates in the context of e-Court. Through a qualitative approach supported by literature studies and in-depth interviews with advocates, this article explores how technology is influencing the role of advocates in the modern legal process. The results show that although technology has accelerated case resolution, advocates are faced with a number of obstacles, such as limitations in digital literacy, difficulties in adopting new technologies, and concerns related to data security and client privacy. In addition, the limited infrastructure in some areas, especially in remote areas, is a challenge in the optimal implementation of e-Court. Furthermore, the study also revealed that e-Court can reduce direct interaction between advocates and courts, potentially affecting the quality of legal defense and representation. Therefore, strategic steps are needed so that advocates can quickly adapt to technological developments, including through training, skill improvement, and adequate infrastructure development. This article emphasizes the importance of clear and inclusive regulations in facing the challenges of digitalization in the legal sector, in order to create a more responsive, efficient, and fair judicial system in the digital era.